Effect of mutualistic and antagonistic bees on floral resources and pollination of a savanna shrub - Quinalha, Marília Monteiro [UNESP]; Nogueira, Anselmo [UNESP]; Ferreira, Gisela [UNESP]; Guimarães, Elza [UNESP] (Elsevier, 2017)
Since Darwin, cheaters have been described in plant-pollinator mutualisms. Bignoniaceae species have a wide interaction network with floral visitors, and most of those interactions are established with cheaters. Thus, our objective was to determine which role each floral visitor plays in a system composed by bees and a Bignoniaceae savanna species. So, here we described the bees’ behaviour and defined experimentally who are the mutualists and cheaters, we described the temporal sequence of interactions, quantified pollen and nectar removal, and checked for the potential effect of robbery damages on pollinator behaviour. Pollinators visited a small number of flowers, mainly in the early morning, while the most frequent cheaters (robbers and thieves) visited the flowers throughout the day, increasing visitation at midmorning, when pollinators had already visited the flowers. We considered medium-sized bees as pollinators, small bees acted only as cheaters, not contributing to seed production. Pollen thieves reduced the amount of male gametes available for pollination, while nectar thieves and robbers were associated with nectar depletion. We did not find any significant difference in the number of pollen grains deposited on the stigmas of flowers with and without robbery damages. In conclusion, when pollinators visit J. caroba flowers in the early morning, there might be a smaller competition pressure among visitors due to the greater amount of resources available, especially in recently opened flowers, and due to the low frequency of cheaters visits, which probably prevents a major negative impact of cheaters on pollination and plant reproduction in this species.
Keywords: Bignoniaceae; Cheaters; Jacaranda caroba; Nectar; Pollen; Pollinators